Gene Drives on the Horizon: Issues for Biosafety. (December 2016) - Heitman, Elizabeth; Sawyer, Keegan; Collins, James P.
In June 2016, the National Academies of Sciences, Engineering, and Medicine published a 220-page report from its multidisciplinary Committee on Gene Drive Research in Non-Human Organisms, which addressed the state of the science of gene drive research and related governance, as well as an array of ethical, social, and legal considerations. Gene drive research is scientifically intriguing and ethically daunting because, unlike other applications of new gene-editing technologies, an effective gene drive is intended to cause the spread of a specific genetic modification through a population and potentially throughout an entire species. This technology holds promise for addressing complex and persistent challenges in public health and ecology but also raises the threat of unintended consequences. Biosafety specialists will have an important role in defining and meeting the need for effective containment, mitigation, and governance strategies for gene drive research. This article reviews the conclusions and recommendations of the committee and recent commentary from leading gene drive researchers, with emphasis on issues in biosafety.